2017
DOI: 10.1007/s00787-017-0965-3
|View full text |Cite
|
Sign up to set email alerts
|

A developmental approach to dimensional expression of psychopathology in child and adolescent offspring of parents with bipolar disorder

Abstract: The aim of this is to describe psychopathology, functioning and symptom dimensions accounting for subthreshold manifestations and developmental status in child and adolescent offspring of parents with bipolar disorder ("high-risk offspring"). The study population comprised 90 high-risk offspring (HR-offspring) and 107 offspring of community control parents (CC-offspring). Direct clinical observations and parental and offspring reports based on selected standardized clinical scales were used to assess offspring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Studies on psychopathology in child offspring of parents with schizophrenia and bipolar disorder, as opposed to adult offspring, are vital because they provide knowledge on early developmental psychopathology long before onset of the fullblown disorders. Indeed, earlier studies have found a high prevalence of a broad spectrum of Axis I disorders and dimensional psychopathology in FHR-SZ children [8][9][10][11][12][13][14][15] as well as FHR-BP children 12,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] . However, many previous clinical studies have weaknesses, such as small sample sizes, use of convenience samples, inclusion of children from different age groups, or lack of a proper control group.…”
mentioning
confidence: 99%
“…Studies on psychopathology in child offspring of parents with schizophrenia and bipolar disorder, as opposed to adult offspring, are vital because they provide knowledge on early developmental psychopathology long before onset of the fullblown disorders. Indeed, earlier studies have found a high prevalence of a broad spectrum of Axis I disorders and dimensional psychopathology in FHR-SZ children [8][9][10][11][12][13][14][15] as well as FHR-BP children 12,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] . However, many previous clinical studies have weaknesses, such as small sample sizes, use of convenience samples, inclusion of children from different age groups, or lack of a proper control group.…”
mentioning
confidence: 99%
“…Evidence supports the role of both genetic and epigenetic alterations as mediators of the intergenerational transmission of mental disorders [11]. Offspring studies also make it possible to monitor the prevalence and developmental changes of subtle expressions of psychopathology, including emotional and behavioural dysregulation, that are more prevalent among these children than in the general population [12]. The expression of psychopathology changes over time and also depends on pubertal status [12].…”
mentioning
confidence: 99%
“…Offspring studies also make it possible to monitor the prevalence and developmental changes of subtle expressions of psychopathology, including emotional and behavioural dysregulation, that are more prevalent among these children than in the general population [12]. The expression of psychopathology changes over time and also depends on pubertal status [12]. Although biological research is accruing [13] researchers have yet to validate with sufficient reliability biomarkers to serve as screening tools for prevention in younger and older offspring of parents with mental disorders.…”
mentioning
confidence: 99%
“…Nevertheless, previous reports in SZ-off and BD-off have documented lower school performance [50][51][52], poorer peer relationships [51,53], lower verbal IQ [54,55], and some childhood developmental difficulties [8], all of which are variables considered to contribute to CR. Although studies comparing SZoff and BD-off in each of these variables are also scarce, some studies have pointed to the fact that SZ-off may experience more difficulties than BD-off in some of these domains [8,52].…”
Section: Introductionmentioning
confidence: 93%